Contributions of chronic tobacco smoking to HIV-associated brain atrophy and cognitive deficits. (15th March 2022) - Liang, Hua-Jun; Ernst, Thomas; Cunningham, Eric; Chang, Linda
Abstract : Objectives: Tobacco smoking is linked to cognitive deficits and greater white matter (WM) abnormalities in people with HIV disease (PWH). Whether tobacco smoking additionally contributes to brain atrophy in PWH is unknown and was evaluated in this study. Design: We used a 2 × 2 design that included 83 PWH (43 nonsmokers, 40 smokers) and 171 HIV-seronegative (SN, 106 nonsmokers, 65 smokers) participants and assessed their brain structure and cognitive function. Methods: Selected subcortical volumes, voxel-wise cortical volumes and thickness, and total WM volume were analyzed using FreeSurfer. Independent and interactive effects of HIV and smoking were evaluated with two-way analysis of covariance on cognitive domain Z -scores and morphometric measures on T1-weighted MRI. Results: Regardless of smoking status, relative to SN, PWH had smaller brain volumes [basal ganglia, thalami, hippocampi, subcortical gray matter (GM) and cerebral WM volumes ( P = 0.002–0.042)], steeper age-related declines in the right superior-parietal (interaction: P < 0.001) volumes, and poorer attention/working memory and learning ( P = 0.016–0.027). Regardless of HIV serostatus, smokers tended to have smaller hippocampi than nonsmokers (−0.6%, P = 0.055). PWH smokers had the smallest total and regional subcortical GM and cortical WM volume and poorest cognitive performance. Conclusions: Tobacco smoking additionally contributed to brain atrophy and cognitive deficits in PWH. The greater brain atrophy in PWH smokers may be due to greater neuronal damage or myelin loss in various brain regions, leading to their poor cognitive performance. Therefore, tobacco smoking may exacerbate or increase the risk for HIV-associated neurocognitive disorders.